Demographic Dividend in Indonesia: Prospect for Economic Development and the Challenge Ahead - Mansur Juned (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Demographically, Indonesia has transformed itself from a "demographic transitional" society, where reductions in mortality led to rapid population growth and subsequent reductions in fertility led to a slower population growth as the result of programs made by government, fertility has declined to below-replacement level, and rapid population ageing is on the horizon, however, Indonesia’s population is still growing than any other countries in Asia. This particular phenomenon is clearly visible in Indonesian economic growth. Today Indonesia is in the phase of high fertility, high mortality and low natural growth. It is important to question whether Indonesian economy will be able to sustain the same rate of growth in the coming years. The paper makes an attempt to study two related issues; the trends and issues of Indonesia’s demographic history and what are the challenges and opportunities that lie ahead for Indonesian Economy vis-a-vis its negative demographic dividend /demographic debt. Keywords: demographic dividend, economic development